Reasons for non-participation of children and adolescents in a large-scale school-based mental health project - Baldofski, Sabrina; Klemm, Sarah-Lena; Kohls, Elisabeth; Mueller, Sophia M. E.; Bauer, Stephanie; Becker, Katja; Diestelkamp, Silke; Eschenbeck, Heike; Hiery, Alisa; Kaess, Michael; Koenig, Julian; Lehner, Laya; et al. (Frontiers in Public Health, 2024)
Background: Non-participation in mental health studies is an under-explored but very important topic. Investigating reasons for non-participation holds promise for the planning of future study designs and recruitment strategies. This study aimed at investigating reasons for children and adolescents (C&A) not participating in a school-based mental health research project. Methods: Data collection took place within the school-based recruitment of a large-scale multi-site project (“ProHEAD-Promoting Help-seeking using E-technology for Adolescents”) in Germany. Participants were N = 534 C&A aged ≥ 12 years attending secondary schools. The present cross-sectional study analyzed anonymous survey data of C&A who themselves or whose parents, respectively, did not provide written consent to participate in the mental health research project. The questionnaire consisted of 14 items covering potential reasons for non-participation, and four free text fields. Besides descriptive statistics, free text field answers were analyzed using qualitative content analysis. Results: Students indicated an average of M = 2.94 (SD = 1.75) reasons for their non-participation in the project. In the descriptive analysis of indicated items, the three most frequently reported reasons for non-participation included students reporting to not be concerned by the topic “mental health” (n = 290, 54.3%), not having returned the consent form to the teacher (n = 175, 32.8%), and not having time for participation (n = 149, 27.9%). In the qualitative content analysis, the most frequently assigned categories were organizational reasons (n = 216, 57.1%), general disinterest in study participation (n = 139, 36.8%), and personal attitudes toward the topic “mental health” (n = 84, 22.2%), such as not being concerned with the topic “mental health” (n = 23, 6.1%) or being too concerned with the topic “mental health” (n = 16, 4.2%).Conclusion: The study provides unique insights into reasons for C&A and their caregivers not participating in a large federally funded mental health research project. The results suggest that in order to increase participation rates, stigma should be reduced, parents as well as teachers should be involved where possible, and the use of incentives might be helpful. The study highlights the importance of assessing reasons for non-participation, especially in online intervention studies on mental health.
Gesehen am 26.06.2024